ОЦІНКА ФІНАНСОВОГО СТАНУ МАШИНОБУДІВНОГО КОМПЛЕКСУ РЕГІОНУ - Zablodska, I.V.; Chumakova, T.M. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2010)
The paper presents the results of the analysis of financial activity of the machine-building complex in Lugansk region. The integral coefficient of the financial state of region’s machine-building complex was calculated. It takes into account the importance and significance of financial coefficients included into it and confirms that the financial state of the machine-building complex in Lugansk region is unsatisfactory.